2013
DOI: 10.1093/jmt/50.3.198
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Neural Effects of Music on Emotion Regulation: Implications for Music Therapy Practice

Abstract: Implications for music therapy practice are discussed and preliminary guidelines for how to use music to facilitate ER are shared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(150 citation statements)
references
References 71 publications
3
143
0
4
Order By: Relevance
“…Even though many of these results are derived from severely traumatised groups, such as holocaust survivors, the accumulated knowledge has nonetheless general and fundamental significance for our understanding of resilience [5–7]. The role of positive emotions such as love and the social bond for human and animal well-being has meanwhile been accepted even in neuroscience [8].…”
Section: Resultsmentioning
confidence: 99%
“…Even though many of these results are derived from severely traumatised groups, such as holocaust survivors, the accumulated knowledge has nonetheless general and fundamental significance for our understanding of resilience [5–7]. The role of positive emotions such as love and the social bond for human and animal well-being has meanwhile been accepted even in neuroscience [8].…”
Section: Resultsmentioning
confidence: 99%
“…Music is a classic means of evoking emotion, and like LSD, it has also been used as an adjunct to psychotherapy (Koelsch 2014;Moore 2013). Music has accompanied ceremonial use of psychedelics for many centuries (Nettl 1956), was a staple component in psychedelic-assisted psychotherapy in the 1950s and 1960s (Bonny and Pahnke 1972;Grof 1980) and remains so today (Bogenschutz et al 2015;Johnson et al 2014;Gasser et al 2014a, b;Grob et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Given that improvisation itself may comprise multiple distinct strands of activity, future research could usefully be focused on how different improvisational practices or interactions may have differential or specific effects on health outcomes, for instance considering the effects of the different practices categorised by Wigram (2004). Publications of research findings should detail with greater consistency the intervention under consideration in terms of how and why improvisation is deployed, as Moore has recently stressed (Moore 2013). Furthermore, a number of key populations have been identified in this review as deriving benefits from improvisation in music therapy.…”
Section: Resultsmentioning
confidence: 99%
“…These interpretations are supported by recent findings that adult patients whose depression and anxiety symptoms improved following improvisational music therapy also showed EEG changes consistent with differences in emotional expression and affect regulation (Fachner et al 2013). Furthermore, a recent systematic review of evidence for the effects of music on emotion regulation (Moore 2013) found four studies of musicians that identified changes in activity while improvising consistent with this function, specifically in the amygdala (Limb and Braun 2008) A number of obstacles to identifying mechanisms for the effects of improvisation on health and well-being are raised in the literature. Improvisation is itself a complex accretion of behaviours and circumstances.…”
Section: D) Emotional Expressionmentioning
confidence: 99%